Faktor-Faktor Yang Mempengaruhi Pemanfaatan Pelayanan Kesehatan Di Klinik Sikes Lanud Pattimura Ambon - Abd Rijal Lapodi; Herlien Sinay; Sunik Cahyawati; Dhiya Permata Puluhatumena (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2024)
The low number of people visiting clinics shows that people are not using health services. In the last two years, the use of the Pattimura Air Base Sikes Clinic has decreased from 2021, the number of patient visits was 1143, decreasing in 2022 to 1052 patients, even in 2023 there was a decrease in patient visits from January to April, where patient visits in January and February were 85 patients, in March 73 patients and in April 54 patients. The aim of this research is to find out what factors influence the use of health services at the Sikes Clinic, Pattimura Air Base. This type of research is quantitative research with a cross sectional approach. The population in this study were all people who visited the Sikes Clinic, Pattimura Air Base. The sample in this study was patients visiting the Sikes Clinic, Pattimura Air Base, the sampling technique used was accidental sampling, the instrument used was a questionnaire. Data were analyzed using the Chi Square test. The results show that there is a relationship between the attitude of health workers (p=0.000), accessibility (p=0.003), health facilities (p=0.000) and the use of health services. Education level (p=0.763) and availability of health workers (p=0.887) showed no relationship with health service utilization.